The Fast-Changing Arctic - Scott Zellen, Barry (Northern Lights, 2013)
In this timely new book, international scholars and military professionals come together to explore the strategic consequences of the thawing of the Arctic. Their analyses of efforts by governments and defence, security, and coast guard organizations to address these challenges make timely and urgent reading. Rather than a single national perspective, The Fast-Changing Arctic brings together circumpolar viewpoints from North America, Europe and Asia for an integrated discussion of strategic military, diplomatic, and security challenges in the high North. Thoughtful analyses are included of different regions, climate issues, institutions, and foreign and security policies. This is an important book for students of international studies, political science, and northern studies. With a Foreword by the Honorable Mead Treadwell and an Afterword by Lawson W. Brigham. With contributions by: Alun Anderson Caitlyn Antrim Rasmus Gjedssø Bertelsen Lawson W. Brigham Ian G. Brosnan Daniel Clausen LtJG Michael Clausen Lassi Kalevi Heininen Nong Hong Rob Huebert Maj. Henrik Jedig Jørgensen P. Whitney Lackenbauer Thomas M. Leschine James Manicom Edward L. Miles Barry Scott Zellen Katarzyna Zysk